The development of laboratory safety management in metals and trace elements testing laboratory - Kreuninl, Paweena; Chaosrimud, Duangkamol; Borisuthil, Benchaporn (Bulletin of Applied Sciences, 2022)
Currently, the development in the capacity of laboratories in Thailand evolves very rapidly resulting in higher risks and adversely health impacts to laboratory workers. However, it is the fact that Thailand does not have acts, regulations or decrees issued to directly help the safety management in laboratories. The study aims to generate recommendations with practical approaches to improve safety management for laboratories of the Department of Science Service (DSS). In this study, the metal and trace elements testing laboratory is selected for study. The use of this laboratory as a pilot laboratory is suitable in term of its functionality and old laboratory design similar to most laboratories in DSS. Moreover, the pilot laboratory does not have systematic safety management although it has been accredited for ISO/IEC 17025. The development of laboratory safety management guideline in this study is determined to provide recommendations to establish good laboratory safety practices that are proper for use in the chemical testing laboratories in DSS. The safety assessment of the pilot laboratory shows an increasing of better safety management. The audits show improving of safety management from 29.5% to 46.2% within 4 months and to 60.2% within 12 months. The results of this study provide practical safety management example and can be used as a guideline for other DSS laboratories to develop effective safety management as well.